1995
DOI: 10.1007/bf00032242
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing legume N2 fixation through plant and soil management

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(80 citation statements)
references
References 90 publications
1
79
0
Order By: Relevance
“…The values of ARA of the nodules were within the range of those reported by Matsunaga et al (1994). Although the low nitrate concentration in the soil resulted in a high nodule fresh weight (Streeter 1986) and enhancement ofBNF (Peoples et al 1995), continuous cropping and environmental factors affected the nodulation and ARA of pigeonpea. The low nodule mass and ARA of pigeonpea in Vertisols may be due to nodule damage caused by Rivellia sp.…”
Section: Discussionsupporting
confidence: 60%
“…The values of ARA of the nodules were within the range of those reported by Matsunaga et al (1994). Although the low nitrate concentration in the soil resulted in a high nodule fresh weight (Streeter 1986) and enhancement ofBNF (Peoples et al 1995), continuous cropping and environmental factors affected the nodulation and ARA of pigeonpea. The low nodule mass and ARA of pigeonpea in Vertisols may be due to nodule damage caused by Rivellia sp.…”
Section: Discussionsupporting
confidence: 60%
“…As a legume, soybean has the capacity to fix a large quantity of atmospheric N 2 , in symbiotic association with Bradyrhizobia (Anuar et al, 1995;Peoples et al, 1995). Summary statistics for controlled experiments reported by Salvagotti et al (2008), showed that soybean can fix up to 337 kg of nitrogen per hectare when inoculated with effective strains of Bradyrhizobium.…”
Section: Introductionmentioning
confidence: 99%
“…The data on contribution of pulses by biological nitrogen fixation and emission from different crops were collected from various published scientific literatures, (Peoples et al,1995, IIPR, 2003, IARI, 2014. The value of GHG emissions in terms of CO 2 Kg equivalent was taken at the rate of 10 US dollar per tonne.…”
Section: Net Returns Based On Natural Resource Valuation (Nr Nrv )mentioning
confidence: 99%